Northern Star : J.S. Plaskett - Broughton, R. Peter (Book collections on Project MUSE., 2018)
Northern Star explores Plaskett's unorthodox and fascinating life from his rural roots near Woodstock through his days as a technician at the University of Toronto to his initiation in astronomy at the Dominion Observatory in Ottawa.